2007
DOI: 10.1158/0008-5472.can-06-2870
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Translocation of the Tumor Marker Pyruvate Kinase M2 Induces Programmed Cell Death

Abstract: Cancer cells often fail to respond to stimuli that normally activate their intrinsic apoptotic machinery. Moreover, they are able to adapt to hypoxia by changing their glycolytic rate. Pyruvate kinase (PK) is a rate-limiting enzyme in glycolysis that is converted to a less active dimer form of PKM2 isoenzyme during oncogenesis. Here, we show that both somatostatin and the structural analogue TT-232 interact with the PKM subtype. We further show that the PKM2 is translocated to the nucleus in response to TT-232… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
129
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(136 citation statements)
references
References 28 publications
3
129
0
3
Order By: Relevance
“…It has been proven that the downregulation of PKM2 activity in cancer cells aids in shunting key glycolytic intermediates toward pathways where they, in turn, are utilized as precursors for lipid, amino acid and nucleic acid synthesis. Therefore, the downregulation of PKM2 activity provides a purposeful divergence from catabolic metabolism aimed at energy production toward an anabolic state aimed at providing the needed resources for rapid cellular construction (33). Research has also shown that PKM2 plays a general role in caspase-and Bcl-independent apoptosis, thereby validating PKM2 as a promising, generally relevant target for the development of anticancer therapies with broad efficacy (34).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven that the downregulation of PKM2 activity in cancer cells aids in shunting key glycolytic intermediates toward pathways where they, in turn, are utilized as precursors for lipid, amino acid and nucleic acid synthesis. Therefore, the downregulation of PKM2 activity provides a purposeful divergence from catabolic metabolism aimed at energy production toward an anabolic state aimed at providing the needed resources for rapid cellular construction (33). Research has also shown that PKM2 plays a general role in caspase-and Bcl-independent apoptosis, thereby validating PKM2 as a promising, generally relevant target for the development of anticancer therapies with broad efficacy (34).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of molecules interact with PKM2 (5,6,8,14,18,19,21,23,24,28,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65). Many of them affect the glycolytic functions of PKM2, which directly regulate the Warburg effect.…”
Section: Nonglycolytic Functions Of Pkm2mentioning
confidence: 99%
“…Recently, it was shown that somatostatin and its structural analogue induces nuclear translocation of M2-PK [88]. Nuclear translocation of M2-PK induced programmed cell death in Cos-7 cells.…”
Section: Il-3-induced Nuclear Translocation Of Pyruvate Kinasementioning
confidence: 99%